Zad.1 Rozwiąże równanie i sprawdź rozwiązanie:
7x - 5 + x = 11 + 5x - 4
Zad.2 Rozwiąż równania:
A) 3(2x + 5( - (2 - x) = 1 - x
B) 8x² - 3(x + 2) = 2x(4x + 3)
C) (1 - 2x)(3x + 2) = 1 - (6x + 4)(x - 1)​


Odpowiedź :

Zadanie 1.

7x - 5 + x = 11 + 5x - 4

7x + x - 5x = 11 - 4 + 5

3x = 12|: 3

x = 4

Zadanie 2.

A) 3(2x + 5) - (2 - x) = 1 - x

6x + 15 - 2 + x = 1 - x

6x + x + x = 1 - 15 + 2

8x = -12|: 8

x = -[tex]\frac{3}{2}[/tex]

x = -1 [tex]\frac{1}{2}[/tex]

B) 8x² - 3(x + 2) = 2x(4x + 3)

8x² - 3x + 6 = 8x² + 6x

8x² - 3x - 8x² - 6x = -6

-3x - 6x = -6

-9x = -6|: (-9)

x = [tex]\frac{2}{3}[/tex]

C) (1 - 2x)(3x + 2) = 1 - (6x + 4)(x - 1)​

3x + 2 - 6x² - 4x = 1 - (6x² - 6x + 4x - 4)

3x + 2 - 6x² - 4x = 1 - (6x² - 2x - 4)

3x + 2 - 6x² - 4x = 1 - 6x² + 2x + 4

3x + 2 - 4x = 1 + 2x + 4

3x - 4x - 2x = 1 + 4 - 2

-3x = 3|: 3

x = -1

Odpowiedź:

7x - 5 + x = 11 + 5x - 4

7x+x-5x=11-4+5

3x=12/:3

x= 4

A) 3(2x=5-2+x)=1-x

6x+3x+x=1-15+6

10x=-8/:2

5x=/-4

B)8x2-3x-2=8x2+6x

8x2-3x-8x2+6x=2

3=/2

C)(1 - 2x)(3x + 2) =1-6x-4x+4

(1 - 2x)(3x + 2)+6x-4x=1+4

(1 - 2x)3x + 2+6x-4=5

3x-6x2+6x=5+2-4

9x-6x2=3

Szczegółowe wyjaśnienie:

mam nadzieje że pomogłam licze na naj